Escherichia coli Survival on Dry Bulb Onions Treated with Crop Protection Sprays Prepared using Contaminated Water in the Treasure Valley Growing Region - Jason Racine; Alexandra Nerney; Samantha Kilgore; Tim Waters; Faith Critzer; Linda J. Harris; Stuart Reitz; Joy Waite-Cusic (Journal of Food Protection)
Contaminated agricultural water has been implicated in produce-associated outbreaks, including dry bulb onions (Allium cepa). This study was designed to quantify risks associated with contaminated water used to prepare crop protection sprays applied immediately before the onset of field curing of dry bulb onions. Laboratory experiments determining the behavior of Salmonella and Escherichia coli in crop protection chemical solutions were performed to guide selection for field use. Field trials were conducted (2022, 2023) in eastern Oregon (Treasure Valley) using two onion cultivars (‘Red Wing’ and ‘Cometa’) inoculated with a rifampicin-resistant E. coli cocktail (3–4 log CFU/100 mL) suspended in fungicide solution or clay suspension, and applied with a backpack sprayer at the end of the growing season. Onions were sampled through the next 4 weeks of field curing and after 1 and 4–5 mos of postharvest storage. In 2022, onions were initially contaminated at a maximum cell density of 48 MPN/onion (Geometric mean (GM): 3.7 MPN/onion). At the end of curing, a single onion (out of 320) tested positive at 2 MPN/onion. In 2022, E. coli was not detected during postharvest storage (n = 160). In 2023, the application of contaminated sprays resulted in a maximum contamination of 275 MPN/onion (GM: 8.6 MPN/onion). At the end of the 2023 curing period, three out of 320 onions (0.9%) had detectable levels of E. coli (1–2 MPN/onion). Three ‘Cometa’ onions from the same plot that were treated with fungicide were positive for E. coli after 5 months of postharvest storage (2, 11, and 83 MPN/onion). These field trials indicate field curing conditions in the Treasure Valley help mitigate risks associated with contaminated water used for applying crop protection sprays. E. coli was detected on a small percentage of onions at low cell density after curing. The single onion with elevated E. coli populations after postharvest storage had internal damage characteristic of bacterial rot.